A simplified benchmark of ultrafine particle dispersion in idealized urban street canyons: A wind tunnel study. (November 2015) - Stabile, L.; Arpino, F.; Buonanno, G.; Russi, A.; Frattolillo, A.
Abstract: The paper proposes a benchmark for computational fluid-dynamic models of ultrafine particle (particles' diameter lower than 100 nm) dispersion in urban street canyons. In particular, an on-scale symmetric street canyon was designed and settled in a wind tunnel considering a perpendicular wind condition. An experimental campaign was carried out to: i) investigate the fluid-dynamic conditions inside the canyon through a Particle Image Velocimetry (PIV), ii) evaluate the uncertainty budget of the PIV measurements, iii) design proper particle injection and sampling systems in the street canyon not influencing the fluid-dynamic conditions of the canyon itself, iv) provide particle number concentration profiles at different sections of the canyon (at different heights on both the canyon facades and at a background level) through ultrafine particle generation (Submicrometer Aerosol Generator 3940, TSI Inc.) and measuring devices (CPC 3775 and SMPS 3936, TSI Inc.). The study can be considered the very first attempt to set a benchmark for ultrafine particle dispersion in street canyons through wind tunnel systems. Highlights: Benchmark for validation of ultrafine particle dispersion models in urban areas. Ultrafine particle dispersion in a on-scale street canyon through wind tunnel. Fluid-dynamic characterization of the aerosol flow through PIV technique. Design of particle injection and sampling systems in the canyon. Measurements of particle concentration and distribution profiles in the canyon.